Analysis of the Self-Confidence Level of Grade 4 Students at SD N 2 Brecong in Entrepreneurship Learning - Arief Muhamad Fachrur Rozi; Siti Fatimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Self confidence is one of the factors that influences learning success. This study aims to analays the level of self-confidence of students in grade 4 at SD N 2 Brecong on entrepreneurial learning. This research was conducted at SD N 2 Brecong class 4 in the 2019/2020 school year. The design of this research is simple descriptive. Data collection techniques using observation and questionnaires with a population of 35 students. Data analysis was performed using descriptive techniques. Based on the results of the study it can be concluded that the confidence of grade 4 students at SD N 2 Brecong is good in their confidence. Entrepreneurial learning becomes a container in developing student learning confidence. The fourth grade students' self confidence developed at SD N 2 Brecong is supported by being independent, active in learning, discipline and responsibility.